Kinetics of gait , postural balance and body mass index during the first, second and third trimester of pregnancy - Caniuqueo, Alexis (2014)
Introduction: Pregnancy is characterized by a set of physiological, psychological, emotional and mechanical changes that can affect health. Objectives: To determine gait and postural balance kinetics behavior and body mass index (BMI) by trimester the pregnancy. Design: Non-experimental, descriptive and correlation study. Setting: Physiology and Biomechanics Laboratory, Universidad Autónoma de Chile. Participants: Pregnant women. Interventions: The sample consisted in 25 20-30 year-old pregnant women selected by non-probabilistic criterion. Gait and postural balance were determined by force to the floor by pressure center reaction behavior in Artoficio gait platforms and postural oscillographs. Seca 700 stadiometer was used to obtain weight and size for BMI calculation. Main outcome measures: March kinetics and postural balance alterations. Results: Significant differences (p<0.05) were found in the different trimesters of pregnancy in the support phase and push power of march, left foot tread duration and work in the pushing phase; significant differences were also found for postural balance in follow up conditions and static posturography front view (p<0.05); BMI showed also significant differences. Conclusions: BMI significant increase could generate alterations in the respective support sub phases of gait kinetics and postural balance in front view and closed eyes conditions.